(untitled) (Experimental biology, 2015)
Defined growth curves of diatoms Achanthes hauckiana (D6), Navicula gastrum (D1г), Nitzshia fonticola (D1а),allocated from freshwater sources Almaty region, on two nutrient media (SAG and Cohn). It is established that the content of carotenoids of diatoms culture not differ from one another, whereas the contents of photosynthetic pigments (chlorophyll A and C) is species-specific. Maximum content of lipid characterized by a culture Nitzshia fonticola (up to 32% of dry weight), minimal (up to 18% of dry weight) – culture Achanthes hauckiana.